Awareness of human papillomavirus among primary healthcare providers in tbilisi and rustavi: cross-sectional study (One Health & Risk Management, 2023)
Introduction. Nowadays the worldwide women population including Georgian women is still at high risk of ovarian cancer. As it is well known, the main cause of ovarian cancer is HPV. For effective HPV prevention globally, assessment of knowledge about Human Papillomavirus in women by healthcare providers is significantly important for positive results for disease prevention. But most importantly to reduce the occurrence of ovarian cancer worldwide, healthcare workers must be fully informed about HPV.Aim. Evaluate primary healthcare providers ‘awareness about HPV infection and prevention.Material and methods. Between June and July 2022, a cross-sectional survey was delivered to primary healthcare personnel in several ambulatories in Tbilisi and Rustavi. To assess the awareness of HPV among primary healthcare workers, adapted versions of HPV awareness evaluation questionnaires were used based on the same studies in different countries. Statistical Analysis was performed in IBM SPSS Statistics 23. We used Fisher’s Exact Test to find any associations between sex and awareness about HPV, working position and awareness of HPV, age and awareness of HPV, workplace location and awareness of HPV. P value
Keywords: HPV awareness; human papillo-mavirus; vaccine; knowledge